RELATIONSHIP OF SNACKING PATTERNS WITH DENTAL CARIES IN SDN 1 JEUMPET STUDENTS, ACEH BESAR REGENCY IN 2022 - Wilis, Ratna; Maulizani, Dea (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Dental caries is a major dental and oral health problem in the world. Dental caries is a disease of dental hard tissue that is closely related to the consumption of cariogenic foods or drinks. Cariogenic foods are sweet foods that can cause dental caries. The large number of street food vendors will encourage students to have a habit of consuming street food, especially during class breaks. Based on the results of the initial data on dental caries examination conducted at SDN 1 Jeumpet, from 15 students, the average dental caries was 3.8 in the moderate category. This study aims to determine the relationship between snacking patterns and dental caries in students of SDN 1 Jeumpet, Aceh Besar District. Using the chi-square test with a value of <0.05. The research was carried out at SDN 1 Jeumpet, Aceh Besar District and was carried out on 19-21 January 2022. The population in this study amounted to 102 students. The sample of this research is all students of SDN 1 jeumpet taken using Random Sampling technique that is as many as 50 students. The results showed that the value obtained was p = 0.034. Based on the results of the study, it was found that the pattern of snacking was not good with dental caries status in the high category of 13 students (50%). Meanwhile, a good snack pattern with dental caries status was found in the moderate category, namely 13 respondents (54.2) with a p value of 0.034 (p<0.05). The results of the chi-square statistical test show that there is a relationship between snacking patterns and dental caries in SDN 1 Jeumpet students, Aceh Besar district in 2022. It can be concluded that there is a relationship between snacking patterns and dental caries. Suggestion: It is expected that students will reduce the pattern of snacking on sweet and sticky foods and it is recommended to increase the consumption of fibrous snacks as daily food and maintain dental and oral hygiene.